TO CLICK BAIT OR NOT: DETECTING AND PREVENTING CLICK BAITS IN FACEBOOK - M.Phil, Ananthan; Babu, S.Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Facebook has been evolved into a powerful tool for communication over recent years. To ensure monetary benefits, a new marketing strategy has been introduced and critiques named it click bait. With headlines designed to entice people to click for monetary benefits, click bait articles published by online news outlets have become a dominant form in Facebook. The aim of this study is to form a detection technique to detect and prevent click baits that appear on Facebook news feeds. The research also investigates the attitude of online readers towards click bait articles. For the analysis, two national acclaimed online websites having more than one million subscribers on their Facebook page were considered. To measure the degree of effects of click baits have on readers, a survey was also conducted. The findings shows that publishers are creating a curiosity gap in readers through their click bait headlines using different lexical techniques. The study also asserts that the use of click bait headlines results in negative effects on perceived credibility in the readers.